"All-in-one" hypergolic metal–organic frameworks with high energy density and short ignition delay. Issue 6 (20th January 2022) - Li, Zhi-Min; Xu, Yi-Qiang; Wang, Chao; Lei, Guo-Rong; Zhang, Rui; Zhang, Lei; Chen, Jian-Hua; Zhang, Jian-Guo; Zhang, Tong-Lai; Wang, Qian-You
Abstract : A type of all-in-one hypergolic MOF has been described, in which CTB ligands as triggers impart active sites for the ignition reaction and imidazole ligands with different substituent groups as bandgap mediators could optimize the hypergolicity. Abstract : Constructing a high performance hypergolic propellant is of vital importance yet challenging. Herein, by taking metal–organic frameworks (MOFs) as a prototypical system, we proposed that co-assembled functional cyanotetrazolylborohydride (CTB) and imidazole (Im) ligands via an "all-in-one" strategy can simultaneously achieve ultrashort ignition delay and high energy density. Experimental analysis combined with DFT calculations elucidated that CTB moieties in MOFs imparted abundant active sites to promote the ignition reaction process. Imidazole ligands with varying substituent groups as bandgap mediators could efficiently adjust the hypergolic performance. As such, the obtained four hypergolic MOFs (Cu-CTB-RIm, R = methyl, ethyl, allyl and vinyl) exhibited intriguing hypergolic ability. This study provides fundamental insights into improving the hypergolic activity of MOFs, and highlights new opportunities for designing advanced hypergolic propellents for modern deep space exploration.